Exploring The Impact of Cooperative Integrated Reading Composition Toward Students’ Reading Ability - Hamid Ismail; Saiful Saiful; Rina Asrini Bakri (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The objective of this study was to find out the improvment of the students’ reading ability at STKIP Kie Raha Ternate in mastery, the reading ability by applying cooperative integrated reading composition. The research population of this study was the second semester students of English education department STKIP Kie Raha Ternate in academic year 2021/2022. It consisted of 7 classes and total populations were 187 students. This research used the purposive sampling technique, and the class English II D was chosen as the sample of the study. The sample were the 30 students. The instrument of this research was the reading test. Reading test was given as pre-test before doing the treatment to know prior ability of the students and post-test after doing treatment to find out the students’ reading comprehension achievement by using cooperative integrated reading composition. The findings showed based on the result of the t-test where the researchers found that there was a significant different between the results of pre-test ad post-test. The difference was seen after comparing it with the value of t-table. There was a significance difference result of the t-test before and after teaching learning process by using cooperative integrated reading composition students post-test was significantly improve. The researchers concluded that the use of the problem based learning strategy improved the students speaking ability and can be used for teaching reading .